STRATEGIC ADMINISTRATION MODEL OF HIGHER EDUCATION FOR REGIONAL ECONOMIC GROWTH IN ZHEJIANG PROVINCE - Guo, Xiangxiang; Boonphadung , Suttipong (วารสารนิสิตวัง, 2026)
Against the backdrop of high-quality economic transformation and higher education reform, strategic administration requires systematic and evidence-based examination. This study adopts an explanatory sequential mixed-methods design integrating quantitative and qualitative approaches. The objectives are to (1) assess the current level of strategic administration, (2) validate its structural dimensions using confirmatory factor analysis (CFA), and (3) construct an empirically grounded model supporting regional economic growth. Quantitative data were collected through structured questionnaires administered to university administrators and faculty members, and analyzed using descriptive statistics and CFA. Qualitative data from semi-structured interviews were examined through content analysis to interpret quantitative findings and refine the model. The findings reveal a relatively high level of strategic administration. CFA confirms a stable seven-dimension framework with satisfactory model fit indices. The integration of quantitative validation and qualitative interpretation results in a Strategic Administration Model consisting of seven interrelated dimensions: Strategic Leadership, Resource Allocation Efficiency, Research and Innovation Capability, University–Industry Collaboration Capability, Internationalization Strategy Development, Human Capital Development, and Knowledge Innovation and Transformation Capability. The model functions as an integrated governance system in which coordinated strategic mechanisms systematically enhance universities’ contributions to sustainable regional economic development.